Efficiency of some theories of drainage for tile drain espacing I. Steady-state flow - Albuquerque, Paulo Emílio Pereira de; Ferreira, Paulo Afonso; Loureiro, Blanor Torres; Bernardo, Salassier (Pesquisa Agropecuaria Brasileira, 2014)
physical laboratory model for determining the distante hetween subsurface tile drain using two soils taken from flooded low lands with a superficial water-table were used to evaluate steady-state flow theories. the soils used were: an Eutrophic Aluvial soil with a clay-loam texture, referred to as a mineral soil, and an association of a Dystrophic Humic-Gley with a Dystrophic organic soil with a sandy-clay texture, referred to as an organic soil the model was used to obtain a saturated hydraulic conductivity from water-table measurements. These data were used to estimate drain spacing from the Donnan-Hooghoudt, Hooghoudt and Kirkham theories and compared to the model dram spacing of 149,0 cm. The Donnan-Hooghoudt theory was the most efficient, giving an average drain spacing of 154,5 cm and a low CV (9,5%) for both soils, as long as the dram tube did not come into contact with the impermeable-layer. In this case the Donnan-Hooghoudt and Hooghoudt theories were inefficient for hoth types of soil. In this study the order of preference of the theories evaluated were: Donnan-Hooghoudt, Hooghoudt and Kirkham.